Pharmacokinetic Appraisal of Carprofen Delivery from Intra-Articular Nanoparticles: A Population Modeling Approach in Rabbits (2021)
Osteoarthritis is frequently treated in veterinary settings with non-steroidal anti-inflammatory drugs (NSAID) such as carprofen (CP). Its action over the articular cartilage can be enhanced by increasing drug uptake into the cartilage, alongside its site of action, and anticipating its rapid distribution towards the bloodstream. A pharmacokinetic study to evaluate carprofen nanoparticles (NP) after intraarticular administration (IA) in rabbits was performed through a modeling allometric approach. The pharmacokinetic analysis of plasma profiles showed a rapid CP distribution outwards the synovial chamber but mainly remaining in plasma (Vc = 0.14 L/5 Kg), according to its high protein-binding. The absorption data modeling showed the occurrence of two different release–absorption rate processes after nanoparticle administration in the synovial space, i.e., a fast rate process causing a burst effect and involving the 59.5% of the total CP absorbed amount and a slow rate process, involving 40.5%. Interestingly, the CP burst effect inside the joint space enhances its diffusion towards cartilage resulting in CP accumulation in about three times higher concentrations than in plasma. In line with these results, the normalized-by-dose area under the concentration vs. time curve (AUC) values after IA were 80% lower than those observed after the intravenous. Moreover, the slower slope of the concentration–time terminal phase after IA administration vs. intravenous (IV) suggested a flip-flop phenomenon (0.35 h-1 vs. 0.19 h-1). Notably, CP clearances are predictive of the pharmacokinetic (PK) profile of CP in healthy humans (0.14 L/h/5 kg vs. 2.92 L/h/70 kg) although an over-estimation has been detected for cats or dogs (10 times and 4 times, respectively). This fact could probably be attributed to inter-species metabolic differences. In summary, despite the limited number of animals used, this study shows that the rabbit model could be suitable for a predictive evaluation of the release enhancement of CP-NP towards the biophase in arthritic diseases not due to sterical retention of the formulation.